2022
DOI: 10.3390/ijerph192114130
|View full text |Cite
|
Sign up to set email alerts
|

Do Current Smokers and Ex-Smokers Who Use Nicotine Vaping Products Daily Versus Weekly Differ on Their Reasons for Vaping? Findings from the 2020 ITC Four Country Smoking and Vaping Survey

Abstract: This study examined reasons why adults who currently smoke or formerly smoked cigarettes use nicotine vaping products (NVPs) by vaping frequency (daily vs. weekly) stratified by smoking status. This cross-sectional study included 3070 adults from the 2020 ITC Four Country Smoking and Vaping Survey (Australia, Canada, England, United States) who reported using a NVP (vaping) at least weekly and who either currently smoke (n = 2467) or formerly smoked (n = 603). Respondents were asked to select the reason(s) the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…This assumes that any smokers newly attracted to vaping would share the same interests in quitting as those who already have some experience. Consistent with the argument that use of vaping might be a conduit to increased interest in quitting [39], we found that preferring use of an ANP to complete cessation was associated with similar factors to interest in quitting overall, in particular increased exposure to vaping and more positive attitudes to it. However, having urges to smoke was also predictive of preferring to switch products, suggesting some smokers may expect an alternative form of nicotine to help reduce cravings while quitting smoking.…”
Section: Discussionsupporting
confidence: 88%
“…This assumes that any smokers newly attracted to vaping would share the same interests in quitting as those who already have some experience. Consistent with the argument that use of vaping might be a conduit to increased interest in quitting [39], we found that preferring use of an ANP to complete cessation was associated with similar factors to interest in quitting overall, in particular increased exposure to vaping and more positive attitudes to it. However, having urges to smoke was also predictive of preferring to switch products, suggesting some smokers may expect an alternative form of nicotine to help reduce cravings while quitting smoking.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, a few participants who reported no intention to quit smoking in the next 3 months (based on the MTSS scale), reported that they were somewhat likely/very likely switching to NVPs and HTPs (22.2% and 20.0% respectively), which may indicate that these products could substitute cigarette smoking in smokers unmotivated to quit and contribute to harm reduction. Similar to previous research among cigarette smokers, we found that the most important reasons for switching to NVPs/HTPs were satisfaction, to reduce harm to themselves and others, to reduce smoking, and to help them stop smoking 53 , 54 . Current prevalence of adult NVP and HTP use in England is 9.3% and 0.2% respectively, though our sample showed similar levels of intention to switch to either product after trying them.…”
Section: Discussionsupporting
confidence: 86%
“…Similar findings regarding NVPs safety were observed in a cohort study in Canada 58 , and it has been suggested that after the US outbreak of vaping-associated lung injury 59 , views on NVPs among smokers deteriorated and many smokers perceiving NVPs at least as harmful to health as cigarettes 60 , 61 . Likewise, studies examining perceptions of harmfulness of HTPs compared to cigarettes suggest that a fair number of smokers considered them to be equally as harmful as cigarettes or they do not know 53 , 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Next, among HTP-cigarette consumers who answered both reasons 23 and 24 (n = 1767) in Table 1 , a three-category quit–reduce composite measure of their intentions for using HTPs as per Yong et al [ 25 ] and Gravely et al [ 26 ] to evaluate NVP-use reasons, was derived and coded as: (1) those who selected quitting smoking as a reason for HTP use; (2) those who selected using a HTP to reduce the number of cigarettes they smoke but did not select quitting smoking; or (3) those who did not select reducing the number of cigarettes they smoke or quitting smoking (selected other reasons only).…”
Section: Methodsmentioning
confidence: 99%